PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KETERAMPILAN SOSIAL SISWA PADA MATA PELAJARAN PKn KELAS IV SD 6 MATARAM - Khairun Nisa (Universitas Hamzanwadi, 2009)
This research is the development of learning material of 4-D model, which is produce the learning materials covering: learning plan, student book, student activity sheet and the result of testing learning. Those learning materials are tried-out by valuators and later tried-out twice at 39 fourth class students of SDN 15 Mataram in the year of 2008/2009 and at 36 student of SDN 6 Mataram. The implementation of the study consists of three stages i.e., (1) Compilation of learning materials covering learning plan (RP), student book, student activity sheets (LKS), gratings, items test of learning result (THB). At this stage, validation from experts is conducted in each learning materials. (2) Implementation of the learning in the try-out class. (3) Implementation of the learning in the real class. Based on the data analysis it is found that the result of the study is in the form of learning materials, activity and social skill of the students is good and reliable. The result of the data analysis descriptively is obtained the effective cooperative skill with the average of RP 1 = 3.6 and RP 2 = 3.5. It can be concluded that this cooperative learning type Jigsaw can improve the social skill of the students and the result of the student learning of SDN 6 Mataram. Keywords: PKn, Cooperative learning type Jigsaw, student’s social skill